Sustainable and inclusive development in left-behind places - Maximilian Benner; Michaela Trippl; Robert Hassink (Review of Regional Research, 2024)
Scholarly work in economic geography and regional science has recently seen a~renewed interest in spatial inequalities, driven significantly by the debate on left-behind places and the resulting geographies of discontent. The plight of left-behind places calls for new place-based policy responses that address the specific challenges of these regions but that at the same time address grand societal challenges such as climate change, biodiversity loss, or pollution with synthetic chemicals. Despite growing attention among economic geographers and regional scientists to either green or inclusive regional development approaches, how to reconcile environmental sustainability and social inclusiveness in highly challenged left-behind places remains poorly understood. This editorial reflects on and critically discusses the literature on left-behind places and distils unifying conceptual characteristics of left-behindness. We argue that left-behindness is a~temporal, relational, multidimensional, discursive, but not deterministic concept. The non-determinism of left-behindness opens up different choices for actors to shape regional futures. Imagining and negotiating these futures involves dealing with difficult potential trade-offs between environmental sustainability and social inclusiveness, some of which are explored by the articles in this special issue.
Keywords: 910; Sustainable and inclusive development; Left-behind places; Regional development; Place-based policies